2015
DOI: 10.1111/exd.12604
|View full text |Cite
|
Sign up to set email alerts
|

Laser capture microdissection followed by next‐generation sequencing identifies disease‐related microRNAs in psoriatic skin that reflect systemic microRNA changes in psoriasis

Abstract: Psoriasis is a systemic disease with cutaneous manifestations. MicroRNAs (miRNAs) are small non-coding RNA molecules that are differentially expressed in psoriatic skin; however, only few cell- and region-specific miRNAs have been identified in psoriatic lesions. We used laser capture microdissection (LCM) and next-generation sequencing (NGS) to study the specific miRNA expression profiles in the epidermis (Epi) and dermal inflammatory infiltrates (RD) of psoriatic skin (N = 6). We identified 24 deregulated mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(93 citation statements)
references
References 51 publications
3
89
1
Order By: Relevance
“…Previous miRNA profiling studies have suggested increased expression of miR-146a/b in lesional skin of psoriasis patients (Lovendorf et al , 2015; Sonkoly et al , 2007). First, we confirmed by RT-qPCR that miR-146a/b are more highly expressed in lesional as compared to non-lesional skin of psoriasis patients and the skin of control individuals (Figure 1a, Supplementary Table S1), however, no correlation with psoriasis severity was found (see Supplementary Figure S1 online).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous miRNA profiling studies have suggested increased expression of miR-146a/b in lesional skin of psoriasis patients (Lovendorf et al , 2015; Sonkoly et al , 2007). First, we confirmed by RT-qPCR that miR-146a/b are more highly expressed in lesional as compared to non-lesional skin of psoriasis patients and the skin of control individuals (Figure 1a, Supplementary Table S1), however, no correlation with psoriasis severity was found (see Supplementary Figure S1 online).…”
Section: Resultsmentioning
confidence: 97%
“…Previous miRNA profiling studies suggested that the expression of miR-146a/b is increased in the lesional skin of psoriasis patients (Lovendorf et al , 2015; Sonkoly et al , 2007). We confirmed this result and demonstrated that miR-146a level is elevated in the epidermis and in less extent in the dermis of psoriatic skin, while miR-146b is increased in both the epidermis and the dermis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they do not encode proteins, microRNAs may also play a role in the immunogenetics of psoriasis [113, 114]. The rs2910164 SNP of miR-146a was associated with an increased risk of psoriasis in one study [115].…”
Section: Immune Genes With Less-well Established Links To Psoriasimentioning
confidence: 99%
“…It is tempting to speculate that aberrant epigenetic silencing of the miR-197 promoter underlies its decreased expression in psoriasis. The mechanism leading to miR-197 silencing, as well to additional alterations in miRNAs in the psoriatic lesion [25,26,50,51], should be further investigated. Study of the epigenetic structure of miR-197 and its putative promoter sequences in the psoriatic genome might partially answer this question.…”
Section: Discussionmentioning
confidence: 99%